Case of Nonspinal Osteomyelitis Due to Bartonella and Review of the Literature. Issue 5 (September 2017) - Joychan, Sonia; Kuchipudi, Yamini; Danielsky, Paul J.; Bovid, Karen M.; Garg, Deepak
Abstract : Abstract: Spine osteomyelitis resulting from Bartonella infection is well described in the literature; however, little is known about nonspinal manifestations of Bartonella osteomyelitis. Here, we describe a case of femur osteomyelitis in a 5-year-old child and review the literature related to nonspinal manifestations of Bartonella . In the 33 cases reviewed, infection of the pelvic girdle was most commonly observed (42%), followed by femur (21%) and humerus infections (21%). Fever was the most common symptom, and interestingly, 18% of patients did not have any history of cat exposure. Osteomyelitis was most commonly identified by magnetic resonance imaging; however, Bartonella serology and tissue polymerase chain reaction testing were also positive when used. Recovery for most patients occurred after combination antibiotic therapy and did not require surgical debridement. In our patient, full recovery was achieved through surgical debridement and stabilization of the bone, followed by antibiotics. Abstract : Fever and limp in a pediatric patient has an extensive differential diagnosis. In this case, report of Bartonella henselae osteomyelitis, there was no known scratch or bite from a cat, but the patient lived on a farm and was exposed to kittens. Biopsy followed by open incision and drainage was performed, with histology revealing necrotizing granulomatous inflammation. Only after serological studies were ordered was the diagnosis confirmed.